TEOLOGI BENCANA PERSPEKTIF AL-QUR’AN - Ana Fithrotul Jannah; Fathurrosyid (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2024)
It is rare for disaster theology discussions to find common ground. Some people believe that natural disaster is sunnatullah (natural law by Allah), that disaster is misfortune or curse from God, and that disaster is an attempt to test someone’s faith and patience. Recently, theoretical explanations have been used to overcome problems in disaster. For instance, geological causes make Indonesia susceptible to disaster. Therefore, we need to understand other elements contributing to the disaster happening. This research aims to answer two study focuses: first, how does al-Quran theologically define disaster? Second, how are disaster response techniques taught by interpreters of Nusantara? This research aims to know the theological meaning of disaster in al-Quran and the way how interpreters of Nusantara teach disaster responses. This research uses a qualitative library to answer two preceding questions. In the collecting data process, the researcher uses three books of interpretation of Nusantara, popular as the primary source, and secondary literature in the form of books, journals, thesis, and other important sources. First, disaster theology is an interpretation of disaster in the view of al-Quran, with its difficulties. Al-Quran uses several phrases to describe disaster, like calamity, slander, or bala’ mentioned in al-Quran in several different letters. Second, it can be concluded from the three interpretations of interpretaters of Nusantara that the did of humans is the root of its disaster, because Allah will never bring disaster to His people without any strong reason. Due to the breadth of Allah’s mercy, His people never undergo negative things.